Kontribusi Kualitas Layanan Ritel di Toko Basmalah Kasiyan Kecamatan Puger dan Pengaruhnya Terhadap Keputusan Pembelian Konsumen - Tri Palupi Robustin (STIE Mandala Jember, 2021)
This study aims to determine the partial effect of physical aspects, reliability, personal interaction, problem solving, policies on purchasing decisions at Kasiyan Basmalah Store and to determine the simultaneous effect of physical aspects, reliability, personal interaction, problem solving, policies on purchasing decisions at Kasiyan Basmalah Store. The population of this study are consumers who buy at the Basmallah Kasiyan Shop, Puger District. The sampling technique used was non-probability sampling, namely Accidental sampling. The analysis used in this study is a multivariate analysis, namely multiple linear regression analysis. The results prove that the physical aspects, reliability, personal interaction, and problem solving have a significant effect on product purchasing decisions and there is no policy influence on purchasing decisions at Kasiyan Basmalah Store.Keywords: purchasing decisions, physical aspects, reliability, personal interaction